The Position and Role of Teachers In islamic Views - Bakar, M. Yunus Abu; Nayyiroh, Azdatil Arifah; Kamila, Khurun In (CV. Edujavare, 2024)
Teachers in the perspective of Islam have a very noble position. Teachers play an important role in guiding, educating, and fostering a generation of Muslims who are knowledgeable, have noble character, and are useful. The purpose of this study is to explore the role of teachers in Islam that has a significant influence on improving the quality of learning. The research method used is the Quantitative Meta-Analysis Method, which is a research method that analyzes the results of various studies that combine the results of several types of scientific research. The results of this study are that the role and participation of teachers in achieving educational goals are very important in character formation, which is very important in shaping the attitudes and behavior of students to become good and moral individuals. Teachers who instill religious, ethical, and moral values ​​in their students contribute to improving morals and ethics in society. By producing a generation with noble character, teachers contribute to building a better society and gain multiple rewards for every deed carried out by the generation they care for.